Afterlives of Indigenous archives: essays in honor of The Occom Circle - Schweitzer, Ivy; Henry, Gordon (Dartmouth College Press, 2019)
"Afterlives of Indigenous Archives offers a compelling critique of Western archives and their use in the development of “digital humanities.” The essays collected here present the work of an international and interdisciplinary group of indigenous scholars; researchers in the field of indigenous studies and early American studies; and librarians, curators, activists, and storytellers. The contributors examine various digital projects and outline their relevance to the lives and interests of tribal people and communities, along with the transformative power that access to online materials affords. The authors aim to empower native people to re-envision the Western archive as a site of community-based practices for cultural preservation, one that can offer indigenous perspectives and new technological applications for the imaginative reconstruction of the tribal past, the repatriation of the tribal memories, and a powerful vision for an indigenous future."
OCLC: 1080555941
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Humanités numériques; 2-Théorie(s) et épistémologies des médias (media studies/médiologie/intermédialités); 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé